Foraging of the sea urchin Paracentrotus lividus (Lamarck, 1816) on invasive allochthonous and autochthonous algae. (August 2021) - Pusceddu, Antonio; Mikhno, Marta; Giglioli, Angelica; Secci, Marco; Pasquini, Viviana; Moccia, Davide; Addis, Pierantonio
Abstract: Attempts to control marine invasive alien species (IAS) with native predators gained contrasting results, so far. To explore the feasibility of this approach to control the invasive marine alga Caulerpa cylindracea, we investigated the foraging behaviour of the sea urchin Paracentrotus lividus on three native macroalgae ( Ulva sp., Penicillus capitatus and Cystoseira compressa ) and on C. cylindracea . The consumption rate of C. cylindracea fresh biomass resulted larger than that of the other algae, when offered separately or in combination. C. cylindracea, however, was not the most attractive food item. The larger consumption rates of C. cylindracea can be explained by its specific caloric content (as assessed by its biochemical composition) that is lower than that of the other algae. Our results confirm that P. lividus can feed on C. cylindracea, but do not fully support its use to control C. cylindracea, unless in conditions where this alga is largely dominant because of other factors. Highlights: Caulerpa cylindracea is part of the sea urchin Paracentrotus lividus diet. Its largest consumption rates depend upon its caloric content. C. cylindracea is not the most attractive food item. P. lividus could control C. cylindracea only where this alga is dominant.